Prevalence of gingival hyperplasia induced by anticonvulsants: A systematic review - Cláudio, Marina Módolo [UNESP] (2021)
Objective: Gingival hyperplasia (GH) is one of the side effects of anticonvulsant drugs. The aim of this study was to verify the prevalence of GH associated with the use of anticonvulsant, through a systematic review. Material and Methods: Systematic search was done at databases Pubmed and Embase between January 1984 and March of 2020 for identification of articles addressing the prevalence of GH associated with the use of anticonvulsant drugs. The methodological index for non-randomized studies (MINORS) was independently assessed for quality in the selected papers. Results: The search identified 4.471 references. Nine articles were selected and evaluated 632 participants. All of the studies included in the systematic review showed a low risk of bias. The anticonvulsants used by patients were carbamazepine, ethosuximide, phenytoin, primidone, phenobarbital, sodium valproate. The studies showed a correlation between different types of anticonvulsants and GH prevalence, with a range from 0% to 73%. Among the anticonvulsants used, phenytoin showed the greatest incidence of GH, varying between 15.61% and 73% in patients. Conclusion: In the analysis of the results obtained in the literature, it is possible to notice that the great majority of studies presented incidence of GH associated with anticonvulsant use. However, further studies are necessary to understand the anticonvulsant action mechanism inducing GH, as well as the prevention forms, given that GH is a significant side effect.